Exercise-based cardiac rehabilitation adaptation protocol during Covid-19 pandemic achieved similar results as compared to non-pandemic usual practice: a single center experience - Anggoro Budi Hartopo; Irsad Andi Arso; Ade Meidian Ambari; Bambang Dwiputra; Basuni Radi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2022)
During the Covid-19 pandemic, exercise-based cardiac rehabilitation (EBCR) faced challenges. Adaptation protocols were implemented to circumvent these challenges. The study aimed to investigate whether the adaptation protocols of EBCR during Covid-19 period influenced the result of cardiac rehabilitation. This was a retrospective cohort study. The subjects were patients who underwent an EBCR program in Dr. Sardjito General Hospital. Yogyakarta, Indonesia. The registry of cardiac rehabilitation was obtained and divided into two periods: non-Covid-19 period and Covid-19 period. During the non-Covid-19 period, 3 EBCR sessions per wk (10-12 total sessions) were performed. During the Covid-19 period, EBCR was reduced to 2 sessions per wk (10-12 total sessions). The functional capacities were evaluated as metabolic equivalents (METs) and exercise test time (min) by treadmill test. A total of 122 subjects completed the EBCR. There were no significant differences in METs and exercise minute achieved between two time periods. Among subjects with different sessions per wk, namely 2, 3, and 4-5 sessions per wk, there were no significant differences in METs (7.01±1.89; 7.23±1.74; and 7.33±2.13, p=0.813) and minutesachieved (6.72±1.94; 6.96±1.96; and 6.81±1.84, p=0.848) in the end sessions. In conclusion, the adaptation of EBCR protocols during the Covid-19 period by reducing the number of sessions per wk has similar results as compared to the usual regular EBCR practice.